(untitled) (Research, Society and Development, 2024)
Objective: To describe and spark reflections on the need for an education strategy that benefits both patients in the cardiovascular context and nurses with work overload in an emergency room with a high demand for daily admissions. Methodology: Experience report addressing the education process in the context of hospitalization in a cardiovascular emergency room, adapting the script by Mussi, Flores & Almeida. Results: Evidence emerged that nurses and patients in a cardiovascular emergency room could benefit from health education using educational technologies focusing on multimedia resources and interactive games. Conclusion of the study: Educational technologies can be incorporated into cardiovascular health education in an emergency room, to the benefit of patients and nurses, due to the potential of this teaching-learning method in the literature. More practical studies are proposed on the benefits of implementing educational technologies on nurses’ workload and improvements to patient treatment.